The Current Role of Platelet Function Testing in Clinical Practice - Mason, George A.; Rabbolini, David J. (Seminars in Thrombosis and Hemostasis, 2021)
Platelet dysfunction, whether hereditary or acquired, may increase an individual's risk of spontaneous, posttraumatic, or postoperative bleeding. Conversely, increased platelet reactivity on antiplatelet agents following vascular (in particular, coronary vascular) intervention may increase the risk of thrombosis and adverse vascular events. The aim of platelet function testing is to identify and characterize platelet dysfunction in these settings to inform bleeding/ thrombosis risk and guide perioperative prophylactic management strategies. A vast array of screening and diagnostic tests is available for this purpose. The successful clinical application of platelet function tests depends on the knowledge of their analytical strengths and limitations and the correct extrapolation of derived results to a particular clinical scenario. This review critically appraises traditional and contemporary platelet function testing focusing on their role in clinical practice.
Keywords: platelet function testing; light transmission aggregometry; platelet reactivity; inherited platelet function disorder